1986
DOI: 10.1007/bf01012110
|View full text |Cite
|
Sign up to set email alerts
|

Selective olfactory choices of the honeybee among sunflower aromas: A study by combined olfactory conditioning and chemical analysis

Abstract: A bioassay based on an olfactory conditioning method simulating the foraging situation in laboratory conditions was coupled with chemical analysis of volatile sunflower blends. Behavioural data obtained from for-agers'responses to volatile fraction point out that honeybees need to use only a limited fraction acting as a "simplified aromatic pattern" of the plant, among hundreds of compounds constituting the whole aroma. This active fraction included 27 polar compounds among which 14 were identified. Extension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…However, some recent work with Marjorana syriaca suggests that whole-plant volatiles can also be important in long-and close-range attraction (Beker et al 1989). The orientation to fragrance by honey bees is most likely a conditioned response (reviewed in Waller et al 1973;Pham-Deleque et al 1986), and there is little evidence that honey bees have innate preferences for particular floral odors (Ribbands 1955;Faegri and van der Pijl 1971;Waller et al 1973;PhamDeleque et al 1986;Henning et al 1992).…”
Section: Beesmentioning
confidence: 96%
“…However, some recent work with Marjorana syriaca suggests that whole-plant volatiles can also be important in long-and close-range attraction (Beker et al 1989). The orientation to fragrance by honey bees is most likely a conditioned response (reviewed in Waller et al 1973;Pham-Deleque et al 1986), and there is little evidence that honey bees have innate preferences for particular floral odors (Ribbands 1955;Faegri and van der Pijl 1971;Waller et al 1973;PhamDeleque et al 1986;Henning et al 1992).…”
Section: Beesmentioning
confidence: 96%
“…A fraction of the volatile compounds that constitute the floral scent can dissolve in the cuticular waxes and become incorporated into the body surface, helping bees to learn and discriminate among several flower species (MASSON 1982, PHAN-DELEGUE et al 1986). The floral fragrances contain more than a hundred compounds including hydrocarbons (WILLIAMS & WHITTEN 1983, PAHN-DELEGUE et al 1986. If the secretion produced by the CSG is dispersed on the bee's body surface and if the hydrocarbons contained in this secretion are able to absorb floral fragrances, it can be hypothesized that gland's secretion also functions in the establishment of the colony's identity, by enabling the acquisition of particular scents originated from food stocks.…”
Section: Discussionmentioning
confidence: 99%
“…Differences between honey types are more quantitative than qualitative, although monofloral honeys can produce compounds specific of the plant of origin (Bouseta et al, 1992;Ferreres et al, 1994). In honey bees, the recognition of complex mixtures was shown to depend not on the whole volatile blend, but rather on a smaller fraction or even a limited number of key-components (for floral odours: Pham-Delègue et al, 1986, 1993Thiéry et al, 1990;Le Métayer et al, 1997; for comb and cuticular waxes: Fröhlich et al, 2000Fröhlich et al, , 2001. Such components could be divided into two categories: (1) those common to the odour of all honeys, and (2) those specific to the plant (or plants) from which the nectar was collected.…”
Section: Discussionmentioning
confidence: 99%
“…Floral aromas are known to be complex mixtures of tens to hundreds of components, but behavioural and electrophysiological studies have shown that floral volatile extracts are recognised on the basis of a limited range of key-components (Pham-Delègue et al, 1986, 1993Thiéry et al, 1990;Le Métayer et al 1997). Honey odours, as flower odours, are characterised by specific compounds, which can be identified using physico-chemical analyses (Bicchi et al, 1982(Bicchi et al, , 1983Bouseta et al, 1992).…”
Section: Introductionmentioning
confidence: 99%